Chromosome Morphology and Heterochromatin Patterns in Paspalum notatum: Insights into Polyploid Genome Structure - Honfi, Ana Isabel (2025)
Background/Objectives: Paspalum notatum is a key multipurpose species native to American grasslands. This study provides, for the first time, a detailed karyotype analysis of diploid (2n = 2x = 20) and tetraploid (2n = 4x = 40) accessions of P. notatum, the most common cytotypes within the species. Methods: The constitutive heterochromatin patterns revealed using CMA-DA-DAPI staining and genome size estimations are novel contributions to the understanding of the N genome in Paspalum. Results: Chromosomes were small (1.1–2.3 µm), with the diploid karyotype comprising nine metacentric pairs (one bearing microsatellites on the short arms, pair 6) and one submetacentric pair. In tetraploids, the diploid karyotype was duplicated. Heterochromatin analysis revealed two CMA++/DAPI− bands located on the short arm and satellite of chromosome 6 in diploids, while tetraploids exhibited two to three CMA++/DAPI− and one to two CMA++/DAPI0 bands. The proportion of GC-rich heterochromatin represented 2.8 and 3.47% of the total chromosome length in diploid and tetraploid cytotypes, respectively. Genome size analysis revealed a reduction in monoploid genome size in tetraploids (1Cx = 0.678 pg) compared to diploids (1Cx = 0.71 pg), consistent with the autopolyploid origin hypothesis. Conclusions: These findings provide essential cytogenetic insights and suggest only minor structural changes in the N genome following polyploidization, which could guide future studies integrating genomic and cytogenetic maps of P. notatum.